Hubungan Penerapan 4 Indikator PHBS Dengan Kejadian Demam Tifoid di Dusun Abbanuangnge Desa Bila Kecamatan Dua Pitue Kabupaten Sidenreng Rappang - Nurfadillah; Fatmah Afrianty Gobel; Sartika (Window of Public Health Journal, 2025)
Clean and Healthy Living Behavior Program for households, Tanrutedong Health Center, had coverage in 2020 of (67%); in 2021, there was a decrease in coverage (56%). For the minimum target of PHBS itself, it has a target achievement of (70)%. The problems that arise include the three highest diseases in the Tanrutedong Health Center, one of which is 90% Typhoid Fever. This study aims to determine the relationship between the implementation of 4 PHBS indicators and the incidence of typhoid fever in Abbanuangnge Hamlet, Bila Village, Dua Pitue District, Sidenreng Rappang Regency in 2022. This type of research is Observational Analytical research with a Cross-Sectional Study approach; this research will be conducted in August and September 2022. The sampling technique in this study uses non-probability sampling in the form of accidental sampling. The population in this study included families in Abbanuangnge Hamlet, Bila Village, Dua Pitue District, and Sidenreng Rappang Regency. There were as many as 171 families, with the Slovin formula of 121 families. The results of the study showed that the use of clean water (p = 0.527) had no relationship with the implementation of typhoid fever, washing hands with clean water and soap (p = 0.391) had no relationship with the implementation of typhoid fever, using healthy toilets (p = 0.560) had no relationship with the implementation of typhoid fever, and eating fruits and vegetables every day (p = 781) had no relationship with the implementation of typhoid fever. The study concluded that there was no relationship between implementing clean water, washing hands with clean water and soap, using healthy toilets, and eating fruits and vegetables every day with typhoid fever. It is hoped that the community will always pay attention to clean and healthy living behaviors to avoid typhoid fever.